Effects of harvesting Mucuna bracteata on the legume biomass and soil properties under mature oil palm - Mohd Noor, Mohd Amir Zunnasri; Sulaiman, Muhammad Firdaus; Wan Abdul Karim Ghani, Wan Azlina; Teh, Christopher Boon Sung (Universiti Putra Malaysia Press, 2021)
The under-utilized legume Mucuna bracteata is a potential biomass resource in Malaysia. A 24-month study was conducted under 10-year-old mature oil palm trees to determine the effects of several harvesting frequencies of M. bracteata on the legume biomass and soil properties. The experimental design was a randomized complete block design (RCBD) for the biomass and a two-factorial RCBD for the soil properties. The treatments were the harvesting frequencies, which were once every two, four, six, and twelve months. The control treatment was without harvest. There were significant effects on the legume’s cumulative biomass, standing biomass, leaf area, nutrient contents, and total nutrient harvested for N, Ca, Mg, and cellulose content. Generally, the more frequent the harvest, the more biomass was obtained, but the more legume standing biomass and leaf area were reduced. Despite the reduction in legume growth and leaf area in the field, harvesting the legume did not affect any of the soil physicochemical properties. The biomass N, Ca, and Mg contents and nutrient harvested were also affected by harvesting. This was due to the production of relatively more young shoots after harvesting, which would remove most of the aboveground plant parts. The cellulose content in the legume also increased for the same reasons. Results showed that harvesting M. bracteata once every six months was an acceptable compromise between collecting large amounts of legume biomass and having a reduced legume growth recovery and leaf area in the field, but yet not detrimentally affecting the soil properties.